Thermal management optimization for large-format lithium-ion battery using cell cooling coefficient - Xie,Y; Hales,A; Li,R; Feng,X; Patel,Y; Offer,G (Journal of The Electrochemical Society, 2022)
The surface cooling technology of power battery pack has led to undesired temperature gradient across the cell during thermal management and the tab cooling has been proposed as a promising solution. This paper investigates the feasibility of applying tab cooling in large-format lithium-ion pouch cells using the Cell Cooling Coefficient (CCC). A fundamental problem with tab cooling is highlighted, the CCC for tab cooling decreases as capacity increases. Coupling low CCCs with greater heat generation leads to significant temperature gradients across the cell. Here, the "bottleneck" that limits heat rejection through the tabs is evaluated. The thermal resistance of the physical tabs is identified to be the main contributor towards the poor heat rejection pathway. A numerical thermal model is used to explore the effect of increased tab thickness and results showed that the cell-wide temperature gradients could be significantly reduced. At the negative tab, increasing from 0.2 mm to 2 mm led to a 100% increase in CCCneg whilst increasing the positive tab from 0.45 mm to 2 mm led to an 82% increasing in CCCpos. Together, this is shown to contribute to a 51% reduction in temperature gradient across the cell in any instance of operation.